Wheat Farmer's Land Consolidation Attitude and Suitable Solutions from Their Viewpoints in (Case Study: Hashtrood Township Rural Area - Ali Shams; Javad Ahadzade; Alireza Abbasi; Hooshmandan Moghadam Fard (Rāhburdhā-yi tusi̒ah-i rūstāyī, 2015)
Proper planning and implementation of sound programs and strategies is vital to  agricultural development. Recognizing current problems and strengths of any section is required in the first step. One of the most important problems in the Iranian agriculture sector is land fragmentation. The purpose of this descriptive-correlational study was to investigate wheat farmers’ attitude and land consolidation solutions from their viewpoints in the Hashtrood Township in year 2013. A group of experts from different majors confirmed the validity of the questionnaire used as our research tool and by conducting a pilot test and the Cronbach’s alpha was calculated to be equal to 0.85 for attitude scale and 0.8 for solution scale, and hence its reliability was verified. The target population consisted of all of the wheat farmers in the Hashtrood Township in the East Azerbaijan province 186 of whom  were selected as samples from 15 villages based on Cochran’s sampling formula and the multi stage randomized sampling method. An analysis of the attitudes of wheat farmers revealed that 67.7 and 32.3 percent of them have unfavorable and neutral attitudes towards land consolidation. Also, there is a significant positive relationship between farming experience and their attitude in land consolidation, but there is a negative relationship between it and their total land segments.  Factor analysis of data revealed that four factors named as deterrent actions, cooperative-common actions, supportive-infrastructural actions and motivational extension actions explained 59.9% of land consolidation solutions by wheat farmers.